2019
DOI: 10.1016/j.nlm.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Memory systems 2018 – Towards a new paradigm

Abstract: The multiple memory systems theory (MMS) postulates that the brain stores information based on the independent and parallel activity of a number of modules, each with distinct properties, dynamics, and neural basis. Much of the evidence for this theory comes from dissociation studies indicating that damage to restricted brain areas cause selective types of memory deficits. MMS has been the prevalent paradigm in memory research for more than thirty years, even as it has been adjusted several times to accommodat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 261 publications
(322 reference statements)
2
39
0
1
Order By: Relevance
“…These three networks are linked together in hub regions, comprising the anterior temporal lobe, posterior middle temporal gyrus, posterior intraparietal sulcus, angular gyrus, and parts of superior and middle frontal gyrus. In general, depending on task demands, for semantic processing various memory systems may be recruited and temporarily linked together, or single subsystems can locally get expanded or diminished, as outlined by a "multiple memory systems theory" (Ferbinteanu, 2019).…”
Section: The Semantic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…These three networks are linked together in hub regions, comprising the anterior temporal lobe, posterior middle temporal gyrus, posterior intraparietal sulcus, angular gyrus, and parts of superior and middle frontal gyrus. In general, depending on task demands, for semantic processing various memory systems may be recruited and temporarily linked together, or single subsystems can locally get expanded or diminished, as outlined by a "multiple memory systems theory" (Ferbinteanu, 2019).…”
Section: The Semantic Systemmentioning
confidence: 99%
“…Based on connectivity analyses, a somewhat extended multidemand network has been described, comprising three major parts: (1) a subcortical sensation/action-related part, (2) a frontal lobe part related to attention, language, working memory, and sensation, and (3) a large-distance network comprising the inferior frontal junction, inferior parietal sulcus, dorsal premotor cortex, and left inferior temporal gyrus, serving, among others, abstract thinking and some language functions (Camilleri et al, 2018). In general, the MDS, and in particular the dorsolateral prefrontal cortex as one or its centers, also serves as a link for connecting various other networks and memory systems, depending on task demands (Ferbinteanu, 2019).…”
Section: The Multiple Demand Systemmentioning
confidence: 99%
“…Multiple memory systems appear to support navigation of the environment including a hippocampal‐dependent “place” system reliant upon external spatial cues and a striatal‐dependent “response” system reliant upon egocentric body turns (Ferbinteanu, 2019; Gold et al, 2013; Johnson, van der Meer, & Redish, 2007; Mizumori, Yeshenko, Gill, & Davis, 2004; Packard & Goodman, 2013; Tolman, 1949). In the present study, place and response strategies were equally effective for learning the location of an appetitive reward (i.e., number of trials to criterion did not significantly differ by behavioral strategy).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, we also observed that VTE decreased in association with learning. Thus, while distinct behavioral strategies contribute to behavioral flexibility across diverse environmental conditions (Ferbinteanu, 2019; Goodroe et al, 2018; O'Doherty, Cockburn, & Pauli, 2017; Packard & Goodman, 2013), a deliberative place strategy may impose additional cognitive demands than a habitual response strategy. Mechanisms that enable an animal to select an appropriate navigational strategy in response to external conditions and/or internal needs are therefore critical for generating optimal behavior (Shelton et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation